PERAN LEMBAGA PERKREDITAN DESA DALAM MEMBERDAYAKAN PEREKONOMIAN MASYARAKAT (STUDI KASUS LPD DESA ADAT PALAKTIYING) - Krismawan, I Wayan Wahyu; Sastra Wijaya, Komang Adi; Purnamaningsih, Putu Eka (CITIZEN CHARTER; Vol 1 No 01 (2021): Administrasi Publik 2021, 2021)
LPD Desa Adat Palaktiying is a village financial institution which aims to improve the welfare of rural communities through economic empowerment of the Desa Adat Palaktiying villagers by providing various credit and savings programs. The research method used in this research is descriptive qualitative method. The technique of determining the informants used in this study is purposive sampling . The data sources used are primary data sources obtained through semi-structured interviews and secondary data sources obtained through documents related to research. While the data collection techniques used were observation, interviews, and documentation. The data analysis technique used is to carry out the stages of data analysis consisting of data reduction, data presentation, and verification. Based on a study using Henry Minzberg's role theory, the results showed that of the three indicators, which is the interpersonal role, the role related to information, the decision-making role, it could run well. Keywords: Role, LPD, Economic Empowerment